2016
DOI: 10.18632/oncotarget.8654
|View full text |Cite
|
Sign up to set email alerts
|

Yin Yang-1 increases apoptosis through Bax activation in pancreatic cancer cells

Abstract: The transcriptional regulator Yin Yang-1 (YY1) is a tumor suppressor known to be overexpressed in pancreatic cancer. We found that overexpression of YY1 promoted apoptosis and increased the expression and mitochondrial localization of the pro-apoptotic Bax protein in pancreatic cancer cell lines. Luciferase reporter, electrophoretic mobility shift (EMSA), and chromatin immunoprecipitation (ChIP) assays revealed binding of YY1 to the BAX promoter. Moreover, YY1 promoted pancreatic cancer cell apoptosis through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
39
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 31 publications
(39 citation statements)
references
References 27 publications
(25 reference statements)
0
39
0
Order By: Relevance
“…[33][34][35] According to our previous study, YY1 is highly expressed and plays the role of a tumor suppressor factor in pancreatic cancer. 14,15 It has been found that high expression of YY1 can inhibit the invasion and metastasis and promote the apoptosis in pancreatic cancer cells. 14,15 In this study, we reveal that YY1 suppresses the abilities of proliferation and migration in pancreatic cancer cells, which is consistent with the anticancer role of YY1in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…[33][34][35] According to our previous study, YY1 is highly expressed and plays the role of a tumor suppressor factor in pancreatic cancer. 14,15 It has been found that high expression of YY1 can inhibit the invasion and metastasis and promote the apoptosis in pancreatic cancer cells. 14,15 In this study, we reveal that YY1 suppresses the abilities of proliferation and migration in pancreatic cancer cells, which is consistent with the anticancer role of YY1in pancreatic cancer.…”
Section: Discussionmentioning
confidence: 99%
“…Human pancreatic ductal adenocarcinoma (PDAC) cell lines BXPC‐3 and PANC‐1 were acquired from the Shanghai Cell Bank (Shanghai, China). Previously, the stable cells of YY1 overexpression or knockdown were already constructed in BXPC‐3 and PANC‐1 cell lines, and the stable cell lines (BXPC‐3‐Vector, BXPC‐3‐YY1, BXPC‐3‐Scramble shRNA, BXPC‐3‐YY1 shRNA, PANC‐1‐Vector, PANC‐1‐YY1, PANC‐1‐Scramble shRNA and PANC‐1‐YY1 shRNA) were selected by culturing in media containing 5 μg/ml puromycin (Sigma, St Louis, MO) . YY1 expression was confirmed by qRT‐PCR and Western blot.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…MDM2 is an oncoprotein, which blocks p53‐mediated transactivation (Mendoza, Mandani, & Momand, ) and has been revealed to be amplified in PC (Dong et al, ). Bax is known as a multidomain proapoptotic protein, and its higher expression signifies better outcomes for PC patients (Haneef, Parvathy, Thankayyan, Sithul, & Sreeharshan, ; J. J. Zhang et al, ). p21 is a crucial target gene of p53 in executing cell cycle arrest (Y. Zhang et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…As a key transcription factor, YY1 regulates its target gene transcription in a very complex manner. YY1 can activate transcription of oncogenes and tumor suppressors, such as c‐Myc , c‐Fos , ERBB2 , cyclooxygenase‐2 , OTX2 , Msx2 , and Bax . YY1 can also repress transcription of oncogenes and tumor suppressors including Has2 , HIF‐2 α , PVT1 , CEBPD , p16(INK4a) , and RB etc.…”
Section: Discussionmentioning
confidence: 99%